Rare-earth oxide materials for q-switched and mode-locked pulse generations / Nur Farhanah Zulkipli - Nur Farhanah , Zulkipli (2021)
Laser devices are an integral part of the technological background of our modern society. Laser light cuts metals and plastics, transmits data over the fiber-optical cabling of internet, reads DVD disks and bar codes, etc. Many applications, such as breakdown spectroscopy, refractive eye surgery, and various time-resolved methods, rely on optical power that is delivered in short or ultrashort pulses. The bite of laser light on the matter is also greatly enhanced by pulsing. Q-switching is a method of producing pulsed laser light by periodically suppressing the optical feedback of a laser resonator. Mode_locking is a technique to produce a shorter pulse width by inducing a fixed-phase relationship between the longitudinal modes of the laser's resonant cavity. Both Q_switched and mode-locked pulses can be realized by a passive technique using a saturable absorber (SA) device. This thesis aims to develop new SA devices based on rare earth oxide (REO) materials. Six new REO materials; Neodymium Oxide (Nd2O3), Samarium Oxide (Sm2O3), Europium Oxide (Eu2O3), Gadolinium Oxide (Gd2O3), Scandium Oxide (Sc2O3) and Yttrium Oxide (Y2O3) have been successfully used to develop new SAs to function as pulse initiator in 1.55 µm region. The newly developed Nd2O3, Sm2O3, Eu2O3, Gd2O3, Sc2O3 and Y2O3 films have a modulation depth of 2.8 %, 33 %, 20 %, 10 %, 16 % and 38 %, respectively and thus suitable for use in Q-switching and mode-locking. For instance, a stable Q-switched operation was achieved by incorporating Eu2O3 film inside an Erbium-doped fiber laser (EDFL) cavity. As the pumping power was increased from 84.0 mW to 125.0 mW, the repetition frequency increased from 60.1 kHz to 68.6 kHz and pulse width reduced from 4.5 µs to 3.6 µs respectively. The Q-switched EDFL was operating at the center wavelength of 1568 nm had a 162 nJ maximum pulse energy and 10.24% slope efficiency. Adding a 100 m SMF in the ring cavity initiated a self-starting mode-locked EDFL and the pulses remained stable within a range of 104.6 to 145.8 mW pump power. At the threshold pump power of 104.6 mW, the mode-locked EDFL operated at a central wavelength of 1565 nm with a repetition rate of 1.8 MHz and pulse width of 3.51 ps. It is found that Y2O3 SA based Q-switched EDFL produced the highest pulse energy of 177.77 nJ at repetition rate of 99.22 kHz when the pump power is fixed at 175.87 mW. In a mode_locked laser, the use of Sc2O3 SA provides the highest pulse energy and peak power of 30.65 nJ and 8.81 kW, respectively. The results show that the prepared REOs can be deployed as a SA for both Q-switching and mode-locking generations.